1995
DOI: 10.1016/s0022-5223(95)70024-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Duraflo II heparin-treated extracorporeal circuits on the systemic inflammatory response in patients having coronary bypass

Abstract: Cardiopulmonary bypass generates a systemic inflammatory response, including the activation of leukocytes, contributing to postoperative morbidity. To evaluate whether the use of heparin-treated extracorporeal circuits could reduce the inflammatory reaction in patients undergoing cardiopulmonary bypass, we conducted a prospective clinical study on 14 patients having coronary artery bypass in whom perfusion was done randomly with either Duraflo II heparin-treated circuits or with nontreated circuits. In both gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 48 publications
1
39
0
1
Order By: Relevance
“…With various ionic preparations or by covalent binding to the surface, heparin can be attached to polymers. Although heparincoating technologies were originally employed to increase antithrombogenicity, other positive impacts for biocompatibility were aggressively reported, such as decreased neutrophil and complement activation, and inhibited proinflammatory cytokine production (1)(2)(3)(4). Currently, a new heparin bonding system, the Jostra Bioline coating system, has become clinically available.…”
mentioning
confidence: 99%
“…With various ionic preparations or by covalent binding to the surface, heparin can be attached to polymers. Although heparincoating technologies were originally employed to increase antithrombogenicity, other positive impacts for biocompatibility were aggressively reported, such as decreased neutrophil and complement activation, and inhibited proinflammatory cytokine production (1)(2)(3)(4). Currently, a new heparin bonding system, the Jostra Bioline coating system, has become clinically available.…”
mentioning
confidence: 99%
“…Recent improvements in biocompatibility of the extracorporeal circuit, such as heparin coatings, have resulted in considerably less blood activation [9-13]. Despite these improvements, however, we and also other investigators reported no reduction in thrombin generation in patients undergoing CPB with the use of a heparin-coated extracorporeal circuit [14-17], whereas others have found evidence of some possible benefit of these surfaces on the coagulation cascade [18].…”
Section: Introductionmentioning
confidence: 80%
“…Interestingly this is not seen, but there would appear to be inconsistencies in previously published work. In some studies cytokine levels have been undetectable [24], but other investigators have reported a rise in cytokines at the onset of in vivo CPB or when the crossclamp is removed [25]. It maybe that IL-8 and TNF are degraded at a rate that at least matches production, or that a larger sample size would show a significant difference between the groups.…”
Section: Discussionmentioning
confidence: 99%